Reduced Expression of GPX3 in Breast Cancer Patients in Correlation with Clinical Significance - Saelee, Pensri; Pongtheerat, Tanett; Sophonnithiprasert, Thanet (Global Medical Genetics, 2020)
Glutathione peroxidase 3 (GPX3) is the main antioxidant enzyme in plasma. Its biological roles are to protect cells from oxidative stress-induced damage. Several studies have been reported the association between GPX3 expression and its correlation with cancer carcinogenesis including breast cancer. The aim of this research was to investigate the GPX3 messenger ribonucleic acid (mRNA) expression in 82 breast tumors and paired normal breast tissues by SYBR green quantitative real-time reverse transcription-polymerase chain reaction and the association with clinicopathological data. Our results show that GPX3 reduced expression was found significantly associated with number of metastatic lymph nodes (odds ratio [OR] = 3.41, 95% confidence interval [CI] = 1.35–8.64, p = 0.01), no distant metastasis (OR = 5.52, 95% CI = 3.74–11.89, p = 0.04), and nonhormone usage breast cancer patients (OR = 0.19, 95% CI = 0.04–0.93, p = 0.04). This finding suggested that GPX3 plays a role in breast carcinogenesis, and might serve as a prognostic biomarker in breast cancer patients.
Keywords: breast cancer; GPX3; antioxidant enzyme; gene expression; real-time reverse transcription-PCR